Lessons Learn from Online Teaching: Challenges for Teacher under COVID - 19 Situations - Satsin, Theerachol; Wongwiseskul, Sresuda (Journal of The Royal Thai Army Nurses, 2021)
The situation of COVID-19 pandemic around the world enhances people to adjust themselves into new normal lifestyles including students in all level of academic institutions. Social distancing forced university to close down. Classrooms, hanging in the Clouds, need no tables, no chairs and no teachers standing in front of the class as usual. Disruptive adjustment happened while learning outcomes still focused on setting standards; these challenged the collaboration between teachers and students in order to turn the changes to be normal practices and reach the optimal outcomes of learning. Faculty of Nursing, Suan Dusit University faced this disruption with confidence that Work-Based Blended Learning and Technological Scaffolding System (WBSC:LMS) is prompt for teacher to handle the Online Teaching. Furthermore, before this crisis, teachers were continually prepared for using online tools for teaching and assessing the learning outcomes. Thus, challenges for teachers under COVID-19 to teach online are day to day lessons for them especially during March to May, 2020. They learned to be flexible and steady turn to dynamic teaching. This article aimed to unfold the online teaching following the proposed model designed by Klaus Schmidt (2004) with strongly belief that well preparing and dynamic teaching will create New Normal for teachers to coach their students through this quickly disruptive period with success.